NORWEGIA A BIZANCJUM W OKRESIE RZĄDÓW HARALDA SROGIEGO (1047-1066) - Maciej Lubik (In Gremium. Studies in History, Culture and Politics, 2012)
NORWAY AND BYZANTIUM DURING THE REIGN OF HERALD HARDRADA (1047-1066)Herald Hardrada is one of the most interesting individuals in the medieval history of Norway. When he was only 15 he was forced to leave his motherland because of a political conflict which resulted in the death of his stepbrother, king Olaf II of Norway. He wandered throughout Eastern European countries as Varangian mercenary fighting under the command of leaders of Kievan Rus and Byzantium. This allowed him to observe a completely different leadership model than that of Western-Christian culture. This had a significant effect on the character of his reign when he came back to Norway. It was particularly visible because of the fact he treated royal authority with clear superiority over the church hierarchy, what was the reason for his criticism in Deeds of Bishops in the Hamburg Church by the German chronicler Adam of Bremen. Moreover, Herald's reign was a great opportunity for strengthening the Byzantine influence in Scandinavia what is confirmed by numerous archaeological sources. Also, a part of the Strategikon of Kekaumenos suggests that after returning to his motherland, Herald did not cut his ties with Byzantium. Western-European elites did not like that as they perceived Herald's close relationship with the empire and the increasing influence of the Eastern church as a threat to Latin Christianity which had been present in Norway for only two decades.